The antimicrobial and antioxidant potentials of Annona species (A. muricata, A. squamosa, and A. reticulata) through leaf infusions - NURMIATI NURMIATI; PERIADNADI PERIADNADI; SONIA FARMILA SYAHRIL; TRI WIDYA EDELWIS (Society for Indonesian Biodiversity, 2024)
Abstract. Nurmiati N, Periadnadi P, Syahril SF, Edelwis TW. 2024. The antimicrobial and antioxidant potentials of Annona species (A. muricata, A. squamosa, and A. reticulata) through leaf infusions. Biodiversitas 25: 3422-3430. This study aimed to determine the antimicrobial and antioxidant potential of infusions derived from dried leaves of Soursop (Annona muricata L.), Sugar Apple (Annona squamosa L.), and Custard Apple (Annona reticulata L.). Using a nested pattern experimental method, this research aimed to evaluate the potential of these plant extracts in inhibiting microbial growth and antioxidant properties. The experiment used in this research is a nested experimental design with 2 factors and 3 replications, where factor A represents the extract type, while factor B represents the test microorganism. The antibacterial assay was conducted using the disk diffusion and dilution methods against Staphylococcus aureus, Escherichia coli, and Candida albicans. Minimum Inhibitory Concentration (MIC) and Minimum Lethal Concentration (MLC) are determined. Antioxidant activity was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, while Total Phenolic Content (TPC) and carotenoid levels were measured using Folin-Ciocalteu and spectrophotometric methods, respectively. The results showed that the infusion of dried custard apple leaves had the highest growth inhibition against S. aureus ATCC 29213, with a zone of inhibition of 10.65 mm. However, these effects were not significantly different for E. coli American Type Culture Collection (ATCC) 25922 and C. albicans. The dried custard apple leaf infusion showed an inhibition rate of 48.58% against S. aureus, compared to the positive control chloramphenicol (0.1 mg/mL), and inhibition rates of 24.57% against E. coli and 28.70% against C. albicans, compared to the positive control fluconazole (0.1 mg/mL). The results revealed that the Minimum Inhibitory Concentration (MIC) of soursop and custard apple leaf extracts against S. was 6.25%, with a Minimum Lethal Concentration (MLC) of 12.5%. The MIC of sugar apple leaf extract against S. aureus was 6.25%, with an MLC of 25%. The antioxidant activity of the soursop leaf extract had the highest antioxidant activity, with the IC50 value of 38.56 ?g/mL. The custard apple leaf extract had the highest polyphenol content (38.97 mgGAE/mL). The fresh sugar apple leaf extract emerged as the leader in carotenoid content, recording an impressive 548.84 ?mol/g. This research revealed the potential bioactivity of the infusions derived from dried leaves of Soursop, Sugar Apple, and Custard Apple for antimicrobial efficacy and potent antioxidant properties. Therefore, they might have the potential as novel therapeutic agents and nutraceuticals.